Pengaruh Media PAKAPINDO (Papan Kantong Pintar Doraemon) terhadap Kemampuan Berhitung Siswa Kelas II SD Negeri 10 Pangkalpinang - Navita Hasybiyah; Sasih Karnita Arafatun; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2024)
This research was motivated by the problem of students needing help counting tens and above and the learning media being less varied, so students quickly get bored in class II of SD Negeri 10 Pangkalpinang. This research aims to determine the effect of PAKAPINDO media on the numeracy skills of SD Negeri 10 Pangkalpinang class II. The type of research used is quantitative research with a quasi-experimental design design. The sampling technique used in this research was total sampling. The sample for this research was 32 students in class II C and 32 students in class II D. The data collection technique used was a test consisting of 10 addition and subtraction material test questions. The data analysis techniques used are the normality test, homogeneity test, and hypothesis test using the related sample t-test (polled variance). The results showed a significant influence on the test results on addition and subtraction material between the experimental and control groups. This is shown in the results of the t-test calculation of related samples (polled variance) with t-count= 2.994 > t-table= 1.999, showing that Ho is rejected and Ha is accepted. The PAKAPINDO influences the numeracy skills of class II students at SD Negeri 10 Pangkalpinang.